The new production of knowledge: The dynamics of science and research in contamporary societies - Gibbons, Michael; Limoges, Camille; Nowotny, Helga; Schwartzman, Simon; Scott, Peter; Trow, Martin (London Sage Publications, 1994)
As we approach the end of the twentieth century, the ways in which knowledge--scientific, social, and cultural--is produced are undergoing fundamental changes. In The New Production of Knowledge, a distinguished group of authors analyze these changes as marking the transition from established institutions, disciplines, practices, and policies to a new mode of knowledge production. Identifying such elements as reflexivity, transdisciplinarity, and heterogeneity within this new mode, the authors consider their impact and interplay with the role of knowledge in social relations. While the knowledge produced by research and development in science and technology is accorded central focus, the authors also outline the changing dimensions of social scientific and humanities knowledge and the relations between the production of knowledge and its dissemination through education. Placing science policy and scientific knowledge within the broader context of contemporary society, this book will be essential reading for all those concerned with the changing nature of knowledge, with the social study of science, with educational systems, and with the correlation between research and development and social, economic, and technological development. "Thought-provoking in its identification of issues that are global in scope; for policy makers in higher education, government, or the commercial sector." --Choice "By their insightful identification of the recent social transformation of knowledge production, the authors have been able to assert new imperatives for policy institutions. The lessons of the book are deep." --Alexis Jacquemin, Universite Catholique de Louvain and Advisor, Foreign Studies Unit, European Commission "Should we celebrate the emergence of a 'post-academic' mode of postmodern knowledge production of the post-industrial society of the 21st Century? Or should we turn away from it with increasing fear and loathing as we also uncover its contradictions. A generation of enthusiasts and/or critics will be indebted to the team of authors for exposing so forcefully the intimate connections between all the cognitive, educational, organizational, and commercial changes that are together revolutionizing the sciences, the technologies, and the humanities. This book will surely spark off a vigorous and fruitful debate about the meaning and purpose of knowledge in our culture." --Professor John Ziman, (Wendy, Janey at Ltd. is going to provide affiliation. Contact if you don't hear from her.) "Jointly authored by a team of distinguished scholars spanning a number of disciplines, The New Production of Knowledge maps the changes in the mode of knowledge production and the global impact of such transformations. . . . The authors succeed . . . at sketching out, in very large strokes, the emerging trends in knowledge production and their implications for future society. The macro focus of the book is a welcome change from the micro obsession of most sociologists of science, who have pretty much deconstructed institutions and even scientific knowledge out of existence." --Contemporary Sociology "This book is a timely contribution to current discussion on the breakdown of and need to renegotiate the social contract between science and society that Vannevar Bush and likeminded architects of science policy constructed immediately after World War II. It goes far beyond the usual scattering of fragmentary insights into changing institutional landscapes, cognitive structures, or quality control mechanisms of present day science, and their linkages with society at large. Tapping a wide variety of sources, the authors provide a coherent picture of important new characteristics that, taken altogether, fundamentally challenge our traditional notions of what academic research is all about. This well-founded analysis of the social redistribution of knowledge and its associated power patterns helps articulate what otherwise tends to remain an--albeit widespread--intuition. Unless they adapt to the new situation, universities in the future will find the centers of gravity of knowledge production moving even further beyond their ken. Knowledge of the social and cognitive dynamics of science in research is much needed as a basis of science and technology policymaking. The New Production of Knowledge does a lot to fill this gap. Another unique feature is its discussion of the humanities, which are usually left out in works coming out of the social studies of science." --Aant Elzinga, University od Goteborg